2011
DOI: 10.1103/physrevlett.106.120601
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Compressibility at Large Scale in Jammed Packings of Size-Disperse Spheres

Abstract: We analyze the large-scale structure and fluctuations of jammed packings of size-disperse spheres, produced in a granular experiment as well as numerically. While the structure factor of the packings reveals no unusual behavior for small wave vectors, the compressibility displays an anomalous linear dependence at low wave vectors and vanishes when q→0. We show that such behavior occurs because jammed packings of size-disperse spheres have no bulk fluctuations of the volume fraction and are thus hyperuniform, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
138
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(150 citation statements)
references
References 19 publications
(45 reference statements)
10
138
1
Order By: Relevance
“…We see that Var(φ R ) is independent ofp, and in contrast to the naive expectation vanishes more rapidly, like ∼ 1/R 3 . This is a signature of the hyperuniformity of jammed packings that has been observed exactly at φ J by earlier analyses of the long wavelength limit of the compressibility [14] and the 2-point spectral density function [15]. The solid line in Fig.…”
Section: Hyperuniformitymentioning
confidence: 78%
See 1 more Smart Citation
“…We see that Var(φ R ) is independent ofp, and in contrast to the naive expectation vanishes more rapidly, like ∼ 1/R 3 . This is a signature of the hyperuniformity of jammed packings that has been observed exactly at φ J by earlier analyses of the long wavelength limit of the compressibility [14] and the 2-point spectral density function [15]. The solid line in Fig.…”
Section: Hyperuniformitymentioning
confidence: 78%
“…We show that the notion of hyperuniformity [14,15], found for packings exactly at φ J , continues to hold in packings above φ J .…”
Section: Introductionmentioning
confidence: 99%
“…We mention that recent, independent work, appearing in preprint form shortly after our own manuscript was posted, [59] has shown that hyperuniformity and vanishing infinitewavelength local-volume-fraction fluctuations in saturated MRJ packings of polydisperse disks are consistent with certain fluctuation-response relations involving a generalized "compressibility." However, this work does not address the appearance of quasi-long-range pair correlations in MRJ hard-particle packings and does not consider MRJ packings of nonspherical particles as in our companion paper [58].…”
Section: Discussionmentioning
confidence: 91%
“…Examples include jamming in amorphous materials [4,5,[7][8][9][10], complete optical band gaps in disordered photonics materials [11][12][13][14][15], and reversibility/irreversibility in periodically driven systems [16][17][18]. Hyperunformity is also important in the arrangement of photoreceptors in the retina [19], and in the large-scale structure of the universe [2].…”
mentioning
confidence: 99%
“…The structural uniformity of a many-body system may be studied in terms of fluctuations in the number [1,2] and volume fraction [3][4][5] of objects inside measuring windows of equal size but different locations. At one extreme, a totally random arrangement exhibits large fluctuations that are Poissonian, such that the volume fraction variance for large L scales as σ φ 2 (L) ∼ 1/L d , where L is the width of the measuring windows and d is dimensionality.…”
mentioning
confidence: 99%